Let us fight as free men : black soldiers and civil rights - Knauer, Christine (Politics and culture in modern America., 2014)
"Today, the military is one the most racially diverse institutions in the United States. But for many decades African American soldiers battled racial discrimination and segregation within its ranks. In the years after World War II, the integration of the armed forces was a touchstone in the homefront struggle for equality -- though its importance is often overlooked in contemporary histories of the civil rights movement. Drawing on a wide array of sources, from press reports and newspapers to organizational and presidential archives, historian Christine Knauer recounts the conflicts surrounding black military service and the fight for integration. Let Us Fight as Free Men shows that, even after their service to the nation in World War II, it took the persistent efforts of black soldiers, as well as civilian activists and government policy changes, to integrate the military. In response to unjust treatment during and immediately after the war, African Americans pushed for integration on the strength of their service despite the oppressive limitations they faced on the front and at home. Pressured by civil rights activists such as A. Philip Randolph, President Harry S. Truman passed an executive order that called for equal treatment in the military. Even so, integration took place haltingly and was realized only after the political and strategic realities of the Korean War forced the Army to allow black soldiers to fight alongside their white comrades. While the war pushed the civil rights struggle beyond national boundaries, it also revealed the persistence of racial discrimination and exposed the limits of interracial solidarity. Let Us Fight as Free Men reveals the heated debates about the meaning of military service, manhood, and civil rights strategies within the African American community and the United States as a whole."--From the dust-jacket front flap.